Ring/Shell Ion Distributions at Geosynchronous Orbit - Thomsen, M. F.; Denton, M. H.; Gary, S. P.; Liu, Kaijun; Min, Kyungguk (Journal of geophysical research. Space physics, 2017)
One year's worth of plasma observations from geosynchronous orbit is examined for ion distributions that may simultaneously be subject to the ion Bernstein (IB) instability (generating fast magnetosonic waves) and the Alfvén cyclotron (AC) instability (generating electromagnetic ion cyclotron waves). Confirming past analyses, distributions with robust ∂fp(v⊥)/∂v⊥ > 0 near v|| = 0, which we denote as “ring/shell” distributions, are commonly found primarily on the dayside of the magnetosphere. A new approach to high‐fidelity representation of the observed ring/shell distribution functions in a form readily suited to both analytical moment calculation and linear dispersion analysis is presented, which allows statistical analysis of the ring/shell properties. The ring/shell temperature anisotropy is found to have a clear upper limit that depends on the parallel beta of the ring/shell (β||r) in a manner that is diagnostic of the operation of the AC instability. This upper limit is only reached in the postnoon events, which are primarily produced by the energy‐ and pitch angle‐dependent magnetic drifts of substorm‐injected ions. Further, it is primarily the leading edge of such injections, where the distribution is strongly ring‐like, that the AC instability appears to be operating. By contrast, the ratio of the ring energy to the Alfvén energy remains well within the range of 0.25–4.0 suitable for IB instability throughout essentially all of the events, except those that occur in denser cold plasma of the outer plasmasphere. Plain Language Summary One year's worth of plasma observations from geosynchronous orbit is examined for ion distributions that may simultaneously be subject to the ion Bernstein (IB) instability (generating fast magnetosonic waves) and the Alfvén cyclotron (AC) instability (generating electromagnetic ion cyclotron waves). Confirming past analyses, ring/shell distributions are commonly found primarily on the dayside of the magnetosphere. A new approach to high‐fidelity representation of the observed ring/shell distribution functions allows statistical analysis of the ring/shell properties. Clear evidence is found for the operation of the AC instability, but only in the afternoon events, which are primarily produced by the energy‐ and pitch angle‐dependent magnetic drifts of substorm‐injected ions. Further, it is primarily at the leading edge of such injections, where the distribution is strongly ring‐like, that the AC instability appears to be operating. By contrast, the IB instability seems to be driven throughout essentially all of the events, except those that occur in denser cold plasma of the outer plasmasphere. These results suggest that fast magnetosonic waves should typically dominate over electromagnetic ion cyclotron waves during most substorm injections. Key Points Ring/shell ion distributions with ∂fp(v⊥)/∂v⊥ > 0 near v|| = 0 are commonly found on the dayside of the magnetosphere A new method for characterizing distributions is used, allowing analytical moment calculation and linear dispersion analysis Ring/shell distributions that are potentially ion Bernstein‐unstable are also subject to the Alfvén cyclotron instability